2023
DOI: 10.2196/49380
|View full text |Cite
|
Sign up to set email alerts
|

Thoughts and Experiences of Behçet Disease From Participants on a Reddit Subforum: Qualitative Online Community Analysis

Jenny Xiaoyu Li,
Elaine Yacyshyn

Abstract: Background Behçet disease (BD) is a type of vasculitis with relapsing episodes and multisystemic clinical features, associated with significant morbidity and impact on patients’ lives. People affected by BD often participate in discussions of their illness experiences. In-person support groups have limited physical accessibility and a relative lack of anonymity; however, online communities have become increasingly popular. Objective This study investiga… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Because users remain anonymous, there may be more incentive for posters to share medical information compared to other platforms that may explicitly state their name, such as Facebook. 9,10,11 One subreddit that has yet to be examined is "r/Cushings." The r/Cushings subreddit is a dedicated space for individuals seeking information, opinions, advice, and support related to Cushing's Disease and Syndrome.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Because users remain anonymous, there may be more incentive for posters to share medical information compared to other platforms that may explicitly state their name, such as Facebook. 9,10,11 One subreddit that has yet to be examined is "r/Cushings." The r/Cushings subreddit is a dedicated space for individuals seeking information, opinions, advice, and support related to Cushing's Disease and Syndrome.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…On its behalf, in Li and Yacyshyn [2023], scholars analysed the posts published over the course of a year in the Reddit subforum ‘r/Behcet’ to investigate the perspectives and experiences of people affected by Behcet’s disease. The authors identified 6 themes and 16 subthemes, including finding connectedness through shared experiences, the struggles of the diagnostic odyssey and sharing or inquiring about symptoms .…”
Section: State Of the Artmentioning
confidence: 99%